2018
DOI: 10.1111/jonm.12610
|View full text |Cite
|
Sign up to set email alerts
|

Health-promoting behaviours of Iranian nurses and its relationship with some occupational factors: A cross sectional study

Abstract: Nurse managers should give more attention to promote nurses' HPBs especially in the areas of stress management and physical activity through implementation of healthy lifestyle programs. Nursing policy makers should give attention to permanent recruitment and improving salary as a strategy to improve nurses' HPBs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 33 publications
1
7
0
Order By: Relevance
“…There are also serious challenges in nursing profession, such as job dissatisfaction, poor social status, nursing shortage, heavy workload and gap between theory and practice. Evidence suggests that Iranian nurses experience higher levels of occupational stress, workload, and burnout in comparison with nurses in other countries; this reduces the quality of nursing care and leads to patient dissatisfaction [27,28]. Despite advances in nurses' educational level, people and government criticize the low quality and safety of care [29].…”
Section: Healthcare System and Nursing Profession In Iranmentioning
confidence: 99%
“…There are also serious challenges in nursing profession, such as job dissatisfaction, poor social status, nursing shortage, heavy workload and gap between theory and practice. Evidence suggests that Iranian nurses experience higher levels of occupational stress, workload, and burnout in comparison with nurses in other countries; this reduces the quality of nursing care and leads to patient dissatisfaction [27,28]. Despite advances in nurses' educational level, people and government criticize the low quality and safety of care [29].…”
Section: Healthcare System and Nursing Profession In Iranmentioning
confidence: 99%
“…As health professionals, nurses should have good health to take care of the patients and also to be a health promoter, as they are role models, advocates, and educators. Nurses are exposed to different risk factors for non-chronic diseases, for instance, stress and anxiety as a result of their workload and daily interaction with sick people, low physical activity, and long working hours [16,17,18]. Their job characteristics make it difficult for nurses to have healthy habits, as studies have reported low self-care in nurses [16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…At the work organisation level, the implementation of a realistic tour with planned breaks should also be focused on [ 63 , 178 ]. Additionally, there should be steady shifts in consultation with employees in tour planning instead of constant shift changes [ 36 ]. Beyond that, employers in the outpatient care sector should place a greater emphasis on the health of their employees in general.…”
Section: Discussionmentioning
confidence: 99%
“…There are already several studies focusing on nurses’ health behaviour, although the majority of the participants were from the inpatient care sector (nurses, nursing students) (e.g., [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ]). Some studies also examined stationary nursing staff, including geriatric nurses and educators [ 55 ] or midwives [ 56 , 57 ].…”
Section: Introductionmentioning
confidence: 99%